Relief of Responsibility: A Fundamental Principle of Market Society - Beyer, Jürgen (Journal of Political Sociology, 2025)
The relief of responsibility stands as a cornerstone shaping market societies, manifesting itself in three pivotal aspects of this economic order: free wage labor, limited liability companies, and market exchange. Free wage labor is a defining feature of capitalism, where human toil is exchanged for monetary compensation. However, historical evidence shows that employers have often neglected their responsibilities to their employees, subjecting them to harsh and deplorable working conditions. This has led to state intervention in the form of legal regulations and social safety nets, effectively transferring responsibility to the governing body. Limited liability companies offer shareholders protection from personal liability, even in cases of corporate misconduct. This allows for rapid capital expansion and economic growth, but it also shifts the burden of accompanying risk onto society as a whole. Market exchange is characterized by depersonalized transactions, which can lead to external effects that impact unsuspecting third parties. For example, environmental degradation and social inequality are often the result of market exchange. The relief of responsibility has a pervasive influence in market societies. It is important to be aware of the relief of responsibility and its implications, so that we can work to create a more just and equitable society.